Visual recognition of conspecifics in the American lobster, Homarus americanus - Gherardi, Francesca; Cenni, Federica; Parisi, Giuliana; Aquiloni, Laura (Animal behaviour, 2010)
For years, individual recognition has been the subject of many studies but, owing to the intrinsic complexity of the phenomenon, it has also been the source of much controversy. The sensory channel(s) used for recognition has also been much discussed. In aquatic invertebrates, vision has been one of the least understood media. We carried out two laboratory experiments using 49 pairs of adult male American lobsters. The first experiment was aimed at investigating the sensory channel/s (smell, sight or the two combined) used by lobsters to get information about the opponent, whereas in the second experiment we tested whether visual experience might allow lobsters to recognize the familiar opponent. Previous exposure to the sight of a conspecific induced lobsters either to avoid the opponent or to skip preliminaries (approaches and threats) and escalate the interaction. However, such changes in the dynamics of fighting were shown only when the opponent was the individual that the experimental lobster had previously seen rather than a generic lobster. This is the first study to provide evidence that lobsters can identify familiar conspecifics by sight, although this does not necessarily mean that they recognize them as individuals. Further studies are needed to clarify this issue.